Networked Personal Development Planning in Support of Lifelong Learning in the Creative Industries - Newland, Barbara; Hanson, Janet; Johnson, Martina (Proceedings of the International Conference on Networked Learning, 2006)
The introduction of Personal Development Planning (PDP) has been a major policy initiative for UK HE. The HE Progress File consists of two elements, the Transcript Record of formal qualifications and the Personal Development Plan, which includes both the processes that are involved in supporting the student in undertaking PDP and also the evidence base of student achievements. In response to the policies many electronic PDP and e-portfolio tools have been developed, both commercially and through nationally funded agencies. This paper considers the issues identified by the PDP4Life regional e-learning project relating to the transfer between institutions of learner records arising from e-PDP outputs and achievements. In particular it focuses on issues that occur in support of employability in the creative industries.